2012
DOI: 10.1080/13546805.2011.582287
|View full text |Cite
|
Sign up to set email alerts
|

Mirrored-self misidentification in the hypnosis laboratory: Recreating the delusion from its component factors

Abstract: These results suggest that hypnotic suggestion can recreate the mirrored-self misidentification delusion from its component factors. Notably, the hypnotic context, itself known to disrupt belief evaluation, can act as Factor 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…The authors found that highly suggestible individuals selectively spent more time washing their hands when the substance was considered potentially harmful and their feeling of knowing had been blocked and experienced less satisfaction from handwashing when their feeling of knowing had been blocked (Woody, Lewis, et al, 2005). In another line of research, hypnotic suggestion has been used to produce compelling analogues of a variety of clinical delusions including mirrored-self misidentification (Connors et al, 2012) and folie à deux (Freeman, Cox, & Barnier, 2013) (for a review, see (Connors, 2015)). Some of these studies have further used this approach to test predictions derived from specific models of delusions (Langdon & Coltheart, 2000).…”
Section: Instrumental Hypnosis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that highly suggestible individuals selectively spent more time washing their hands when the substance was considered potentially harmful and their feeling of knowing had been blocked and experienced less satisfaction from handwashing when their feeling of knowing had been blocked (Woody, Lewis, et al, 2005). In another line of research, hypnotic suggestion has been used to produce compelling analogues of a variety of clinical delusions including mirrored-self misidentification (Connors et al, 2012) and folie à deux (Freeman, Cox, & Barnier, 2013) (for a review, see (Connors, 2015)). Some of these studies have further used this approach to test predictions derived from specific models of delusions (Langdon & Coltheart, 2000).…”
Section: Instrumental Hypnosis Researchmentioning
confidence: 99%
“…By contrast, hypnosis is also often used to induce and modulate specific cognitive and perceptual states in order to test predictions regarding the features of these phenomena (instrumental research). Instrumental research represents a valuable approach because suggestion can sometimes permit the flexible control of otherwise liminal or intractable phenomena in a controlled context (e.g., delusions; (Connors, Barnier, Coltheart, Cox, & Langdon, 2012)), thereby allowing for the possibility of modeling different phenomena, or testing otherwise challenging predictions (Cox & Bryant, 2008). Instrumental research can be further conceptually divided into modeling studies, which aim to establish and validate a hypnotic analogue of a phenomenon and hypothesis-driven studies, whose objective is to use a hypnotic analogue to test predictions regarding a specific phenomenon.…”
Section: Instrumental Hypnosis Researchmentioning
confidence: 99%
“…One such application is in the study of clinical disorders (Kihlstrom, 1979). In previous work, we used hypnotic suggestion to disrupt self-recognition and “model” the neuropsychiatric mirrored-self misidentification delusion, the belief that one’s reflection in the mirror is a stranger (e.g., Connors et al, 2012a). The current experiment extends this work by using hypnotic suggestion to disrupt face processing while testing both self-recognition and face recognition across different visual media.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a suggestion for impaired face processing or mirror agnosia may produce the content of the delusion (Factor 1), hypnosis by itself may disrupt belief evaluation (Factor 2; Connors et al, 2012a,b, 2013). People tend to accept ideas during hypnosis that they would normally reject in an ordinary, everyday state of consciousness (Shor, 1959).…”
Section: Introductionmentioning
confidence: 99%
“…This is important because some clinical patients with the delusion recognise themselves in photographs or handheld mirrors and recognise other people in the mirror, despite maintaining that their own reflection is a stranger (Breen et al, 2001;Feinberg, 2001). Connors et al (2014a) gave 22 highs and 20 lows suggestions for either impaired self-face recognition (the Factor 1 suggestion from Connors et al, 2012a) or impaired recognition of all faces (prosopagnosia). They tested whether participants recognised themselves in a mirror, photograph, live video feed, and a handheld mirror.…”
Section: Impaired Face Processing As Factormentioning
confidence: 98%